Concertación para la erradicación de la violencia contra las mujeres en el distrito de Villa El Salvador 2019-2021 - Reyes Allpoc, Karla Paula (Pontificia Universidad Católica del Perú, 2023)
This study critically analyzes the strategies implemented by the District Coordination Instance (IDC) of Villa El Salvador to prevent, sanction, and eradicate violence against women. It employs a mixed approach, combining qualitative documentary analysis and interviews with key actors, with a quantitative component through a Likert questionnaire applied to IDC members. Its objectives are: a) To analyze the IDC's intersectoral management model against gender-based violence, b) To identify management tools and concrete actions developed, and c) To evaluate the impact of the participation of women's organizations. Tools such as district plans have enabled the implementation of local public policies, while training programs have strengthened capacities and promoted cultural changes.The study concludes that the IDC has consolidated an effective model based on intersectoral articulation, active participation of actors, and empowerment of women's organizations, contributing to more equitable and violence-free societies. This experience sets a valuable precedent as a model for other similar instances.

Este estudio analiza de manera crítica las estrategias implementadas por la Instancia Distrital de Concertación (IDC) de Villa El Salvador para prevenir, sancionar y erradicar la violencia contra las mujeres. Emplea un enfoque mixto, combinando análisis documental cualitativo y entrevistas a actores clave, con un componente cuantitativo a través de un cuestionario Likert aplicado a miembros de la IDC. Sus objetivos son: a) Analizar el modelo de gestión intersectorial de la IDC contra la violencia de género, b) Identificar herramientas de gestión y acciones concretas desarrolladas, y c) Evaluar el impacto de la participación de organizaciones de mujeres. Las herramientas como planes distritales han permitido implementar políticas públicas locales, mientras que los programas de capacitación han fortalecido capacidades y promovidos cambios culturales. El estudio concluye que la IDC ha consolidado un modelo eficaz basado en la articulación intersectorial, participación activa de actores y empoderamiento de organizaciones de mujeres, contribuyendo a sociedades más equitativas y libres de violencia. Esta experiencia sienta un valioso precedente como modelo para otras instancias.
Coordination for the Eradication of Violence Against Women in the District of Villa El Salvador 2019-2021
Keywords: District Coordination Body; Elimination of violence; Joint; Strategy; Active member; Instancia Distrital de Concertación; Eliminación de la violencia; Articulación; Estrategia; Miembros activos; https://purl.org/pe-repo/ocde/ford#5.06.00